Geographical range expansion of alien birds and environmental matching. (4th November 2016) - Su, Shan; Cassey, Phillip; Dyer, Ellie E.; Blackburn, Tim M.
Abstract : The international wildlife trade is a significant source of introduced alien species, some of which proceed to become invasive and cause negative environmental and economic effects. However, not all introduced aliens establish viable populations, and it is important to identify the factors that determine establishment success. We explore the role of environmental suitability (including anthropogenic influences, climate and habitat types) in the establishment success of alien bird species introduced to Taiwan. Using maximum entropy modelling, we employed a recursive feature elimination and Akaike information criterion (AIC)‐based stepwise model selection approach to assess whether the environmental suitability, native range size, body size, residence time and the numbers of birds for sale in the shops affect variation in the extent of alien bird range size in Taiwan. We show that species with larger native range sizes and larger body sizes tend to have larger alien range sizes in Taiwan. There was no effect of environmental suitability on alien range size in Taiwan, but environmental suitability influenced the establishment success of bird species there.